2012
DOI: 10.1111/j.1949-8594.2011.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceptions of Single‐Gender Science and Mathematics Classroom Experiences

Abstract: While participating in single-and mixed-gender science and mathematics classes, ninth-grade urban high school students' (n = 118) academic self-concept, self-efficacy, and school climate perceptions were examined. Their perceptions were measured quantitatively from the Fennema-Sherman Mathematics (modified for Science) Attitude and the Patterns of Adaptive Learning scales. Five factors arose from each instrument: confidence/efficacy, utility, instruction, climate, and anxiety/performance avoidance. Comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The results of statistically significant findings on mathematics self-concepts amongst boys in coed school confirm earlier findings that indicate higher self-concepts among boys (Else-Quest et al 2010;Marsh et al 2013;McGraw et al 2006;Sullivan 2009) and contradict studies that show no effect (e.g., Nagengast et al 2013). Findings that indicates no statistically significant difference in school type attest to other studies (Brown & Ronau 2012;Nagengast et al 2013;Signorella et al 2013), but contradict findings that indicate higher mathematics self-concepts among girls in single-sex schools (Belcher et al 2006;Marsh et al 2013;Riordan 1990) and for boys in single-sex schools (Githua and Mwangi 2003;Sullivan 2009). Findings of reported high mathematics self-confidence amongst girls in single-sex schools confirm earlier studies (Belcher et al 2006;Eshun 2004;Mallam 1993;Nyala 2010;Rowe 1988).…”
Section: Differences On the Vom Constructssupporting
confidence: 78%
See 1 more Smart Citation
“…The results of statistically significant findings on mathematics self-concepts amongst boys in coed school confirm earlier findings that indicate higher self-concepts among boys (Else-Quest et al 2010;Marsh et al 2013;McGraw et al 2006;Sullivan 2009) and contradict studies that show no effect (e.g., Nagengast et al 2013). Findings that indicates no statistically significant difference in school type attest to other studies (Brown & Ronau 2012;Nagengast et al 2013;Signorella et al 2013), but contradict findings that indicate higher mathematics self-concepts among girls in single-sex schools (Belcher et al 2006;Marsh et al 2013;Riordan 1990) and for boys in single-sex schools (Githua and Mwangi 2003;Sullivan 2009). Findings of reported high mathematics self-confidence amongst girls in single-sex schools confirm earlier studies (Belcher et al 2006;Eshun 2004;Mallam 1993;Nyala 2010;Rowe 1988).…”
Section: Differences On the Vom Constructssupporting
confidence: 78%
“…Examining ninth-grade students' attitudes toward learning mathematics (e.g. confidence), science and school climate perceptions, Brown and Ronau (2012) found no significant difference in males' or females' attitudes toward learning mathematics or science, even when segregated into single-sex or coed classes. In Kenya, Githua and Mwangi (2003) found higher mathematics self-confidence and higher mathematics self-concept amongst boys in single-sex schools than amongst girls in single-sex and coed schools.…”
Section: Self-beliefsmentioning
confidence: 87%
“…For us, the questions are about what it is like for particular students to be in single-sex mathematics classes in public schools-understanding that different students can have different experiences and can generate different perspectives and understandings of their experiences (Eliot, 2011). For example, a few researchers did not conclude the implementation of single-sex educational settings to affect students' experiences differently than coeducational educational settings (Brown & Ronau, 2012;Yates, 2011). Other researchers found that student participants did not enjoy single-sex classes (Hoffman, Badgett, & Parker, 2008), while student participants in a study conducted by Spielhagen (2008) seemed to have a positive disposition and experience, which generally decreased from sixth grade to eighth grade.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Fueled in part by this lack of scholarly consensus on single‐sex education efficacy, there continues to be interest in evaluating the effect single‐sex groupings within coeducational schools have on students’ perceptions of the classroom environment and of their academic self‐concepts in mathematics and science (Brown & Ronau, ). In the three decades since Rowe () pointed out the use of single‐sex classes as an intervention strategy to increase participation and achievement of either boys or girls in mathematics and science, studies focused on the impact of single‐sex instruction on self‐concept at the school and classroom level have been equivocal (Belcher, Frey, & Yankeelov, ; Jackson, ; Smithers & Robinson, ; Younger & Warrington, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the three decades since Rowe (1988) pointed out the use of single-sex classes as an intervention strategy to increase participation and achievement of either boys or girls in mathematics and science, studies focused on the impact of single-sex instruction on self-concept at the school and classroom level have been equivocal (Belcher, Frey, & Yankeelov, 2006;Jackson, 2002;Smithers & Robinson, 2006;Younger & Warrington, 2006). Whereas some studies have pointed to significant differences in students' selfconcept based on the type of educational setting (Kessels & Hannover, 2008;Sullivan, 2009), others have not found any significant differences in comparisons of single-sex settings to coeducational settings (Brown & Ronau, 2012;Riordan, 1990). These murky findings are not restricted to mathematics.…”
Section: Introductionmentioning
confidence: 99%